2010
DOI: 10.1021/ml100138q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Omecamtiv Mecarbil the First, Selective, Small Molecule Activator of Cardiac Myosin

Abstract: We report the design, synthesis, and optimization of the first, selective activators of cardiac myosin. Starting with a poorly soluble, nitro-aromatic hit compound (1), potent, selective, and soluble myosin activators were designed culminating in the discovery of omecamtiv mecarbil (24). Compound 24 is currently in clinical trials for the treatment of systolic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 17 publications
1
71
0
3
Order By: Relevance
“…A small-molecule activator specific for cardiac myosin II was discovered in a high-throughput screen for compounds that activate cardiac myosin in a reconstituted sarcomere or myofibril assay (Morgan et al, 2010). Tests of the optimized compound, omecamtiv mecarbil, showed that it accelerates P i release and ATP hydrolysis by cardiac myosin in the presence of actin, but slows P i release and ATP hydrolysis in its absence (Malik et al, 2011).…”
Section: Myosin Activatormentioning
confidence: 99%
“…A small-molecule activator specific for cardiac myosin II was discovered in a high-throughput screen for compounds that activate cardiac myosin in a reconstituted sarcomere or myofibril assay (Morgan et al, 2010). Tests of the optimized compound, omecamtiv mecarbil, showed that it accelerates P i release and ATP hydrolysis by cardiac myosin in the presence of actin, but slows P i release and ATP hydrolysis in its absence (Malik et al, 2011).…”
Section: Myosin Activatormentioning
confidence: 99%
“…Indeed, interactions with these steps may provide several options to regulate contractility (Solaro 2009;Solaro 2010;Sun et al 2008). Probably the best of these strategies may be the application of myosin activators which increase the force of contraction by interacting directly with the myosin heavy chain, as omecamtiv mecarbil, the first selective cardiac myosin activator, does (Morgan et al 2010). …”
mentioning
confidence: 99%
“…CK-1213296 was free of this effect, but inhibited the CYP 1A2 enzyme. All side-effects were successfully eliminated from CK-1317138, and the optimized structure was achieved by CK-1827452, omecamtiv mecarbil (Morgan et al 2010). This latter molecule was more potent by one order of magnitude than its ancestor, CK-1317138 .…”
mentioning
confidence: 99%
“…Omecamtiv mecarbil, ativador seletivo da miosina cardíaca, é a primeira molécula de uma nova classe de drogas inotrópicas positivas que age por ativação direta da miosina cardíaca, destituída de efeitos indesejáveis, como o aumento do consumo de oxigênio, arritmia e aumento da frequência cardíaca 308,309 . Estudos recentes de fase II demonstram que esta medicação pode melhorar a função cardíaca 310,311 , porém não existem grandes estudos clínicos com desfechos de mortalidade e análise de segurança.…”
Section: Ativadores Da Miosina Cardíaca (Omecamtiv Mecarbil)unclassified